PENINGKATAN PEMAHAMAN METODE SELEKSI UNTUK MENDAPATKAN BIBIT ITIK UNGGUL DI DESA TAMBAKSOGRA KECAMATAN SUMBANG KABUPATEN BANYUMAS - Novita Hindratiningrum Novi; Setya Agus Santosa (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Universitas Nahdlatul Ulama Purwokerto, 2023)
Efforts to increase livestock production and livestock products can be carried out through the fields of breeding (genetic = seeds), nutrition and management. The field of breeding aims to increase the productivity (production and reproduction characteristics) of livestock by increasing their genetic quality. Improving the genetic quality of livestock can be done in two ways, namely selection and the mating system. The purpose of this activity is to introduce livestock breeding technology for the formation of superior local duck seeds to breeders and to initiate the formation of local duck breeding units or centers. The method used is technology transfer and the application of nursery patterns with individual selection methods. Technology transfer is carried out through counseling and discussion. The conclusions from the counseling results are (1) to pioneer the establishment of a unit or duck breeding center at the farmer level it needs to be supported by good production records; (2) farmers can understand that the application of breeding technology can increase production in the long term; (3) there is an increase in the knowledge of the participants, as evidenced by an increase in value at the end of the activity. Keywords : selection method; nurseries; ducks